2010
DOI: 10.1371/journal.pone.0012308
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Pluripotency in Human Embryonic Stem Cells Directly Correlates with an Increase in Nuclear Zinc

Abstract: The pluripotency of human embryonic stem cells (hESCs) is important to investigations of early development and to cell replacement therapy, but the mechanism behind pluripotency is incompletely understood. Zinc has been shown to play a key role in differentiation of non-pluripotent cell types, but here its role in hESCs is directly examined. By mapping the distribution of metals in hESCs at high resolution by x-ray fluorescence microprobe (XFM) and by analyzing subcellular metal content, we have found evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…This is consistent with the abundance of zinc-finger domain regulatory proteins in the nucleus and with observations in other eukaryotic cell types. 20 Smaller concentrations of this element were observed in the cell wall/apoplast regions of the cell, where calcium was the most abundant element. This is befitting the role of calcium in neutralizing and crosslinking negative charges, such as those of pectins, in cell walls.…”
Section: Resultsmentioning
confidence: 98%
“…This is consistent with the abundance of zinc-finger domain regulatory proteins in the nucleus and with observations in other eukaryotic cell types. 20 Smaller concentrations of this element were observed in the cell wall/apoplast regions of the cell, where calcium was the most abundant element. This is befitting the role of calcium in neutralizing and crosslinking negative charges, such as those of pectins, in cell walls.…”
Section: Resultsmentioning
confidence: 98%
“…In examining the growth of human embryonic stem cells, taking a systems biology approach to examining entire colonies of cells and all the first row transition metals, we also found that the amount of zinc present in cells directly correlated with their differentiation (Wolford, Chishti et al 2010). The images in Figure 1, of stem cells differentiated with retinoic acid, are particularly illustrative.…”
Section: A New View Of Zinc From Xfmmentioning
confidence: 76%
“…The "stemness" of the cell is maintained by a balance between proteins that promote differentiation and proteins that maintain pluripotency [2,3]. We have begun to explore whether the nuclear zinc influx that we have observed during differentiation [4] is biologically relevant to the "stemness" of the cell. We have published that mitotic chromosomes exclude zinc [4], suggesting that zinc is excluded from heterochromatin.…”
Section: Immunofluorescence: Providing a Framework For The Picturementioning
confidence: 99%
“…We have begun to explore whether the nuclear zinc influx that we have observed during differentiation [4] is biologically relevant to the "stemness" of the cell. We have published that mitotic chromosomes exclude zinc [4], suggesting that zinc is excluded from heterochromatin. This result calls into question the postulate of zinc binding to histones in condensed chromatin [5,6].…”
Section: Immunofluorescence: Providing a Framework For The Picturementioning
confidence: 99%
See 1 more Smart Citation